Extraction, Phytochemical Screening And In-Vitro Evaluation Of Anti-Oxidant Properties Of Commicarpus Chinesis (Aqueous Leaf Extract) - MANAS BOXI; Y.RAJESH; V.RAJA KUMAR; B.PRAVEEN; K.MANGAMMA (International Journal of Pharma and Bio Sciences, 2010)
The present investigation deals with the extraction of leaves of Commicarpus chinensis, preliminary phytochemical screening and evaluation of antioxidant activity using various in-vitro methods. The leaves were subjected to extraction by percolation using water as extracting solvent. Preliminary phytochemical screening reveals the presence of steroids, tannins, flavonoids, saponins, carbohydrates and proteins. The extracts were subjected to evaluation for antioxidant activity by DPPH free radical scavenging method, nitric oxide radical scavenging method and reducing power determination. The concentration that inhibited 50 % of the free radicals was determined. The aqueous extract showed significant activity as compared with the standard. IC50 values for aqueous extract of Commicarpus chinensis, and Ascorbic acid was found to be 86.03 µg/ml and 56.73µg/ml respectively for DPPH method and 73.63 µg /ml and 59.29 µg /ml respectively for Nitric oxide radical scavenging method. The reducing capacity serves as significant indicator of antioxidant activity. The reducing power increased with the increasing concentration of sample. The activity of these extracts can be attributed to the presence of tannins, saponins and flavonoids.